Update on schizophrenia and bipolar disorder: focus on cariprazine - Roberts RJ (Dove Medical Press, 2016)
Rona Jeannie Roberts,1 Lillian Jan Findlay,2 Peggy L El-Mallakh,2 Rif S El-Mallakh1 1Mood Disorders Research Program, Department of Psychiatry and Behavioral Sciences, University of Louisville School of Medicine, Louisville, 2School of Nursing, University of Kentucky, Lexington, KY, USA Abstract: Schizophrenia and bipolar disorder are severe psychiatric disorders that are frequently associated with persistent symptoms and significant dysfunction. While there are a multitude of psychopharmacologic agents are available for treatment of these illnesses, suboptimal response and significant adverse consequences limit their utility. Cariprazine is a new, novel antipsychotic medication with dopamine D2 and D3 partial agonist effects. Its safety and efficacy have been investigated in acute psychosis of schizophrenia, bipolar mania, bipolar depression, and unipolar depression. Efficacy has been demonstrated in schizophrenia and mania. It is unclear if cariprazine is effective in depression associated with unipolar or bipolar illness. Adverse consequences include extrapyramidal symptoms including akathisia, and various gastrointestinal symptoms. The US Food and Drug Administration (FDA) has recently approved cariprazine. This review will provide clinicians with basic information regarding the research program of cariprazine. Keywords: cariprazine, dopamine D3 receptor, dopamine D2 receptor, bipolar disorder, mania, bipolar depression, schizophrenia